Kepentingan Bezit, Levering, Verjaring, Bezwaring, dan Beslag terhadap Pembedaan Benda dalam Hukum Kebendaan Indonesia - Muhammad Faisal (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2022)
Indonesian property law is regulated in the second book of the Indonesian Civil Code originating from the Dutch Burgerlijk Wetboek voor Indonesia (BW) which has been compiled and codified based on the principle of concordance with the Dutch Civil Code, regulated on March 3, 1948 through Staatsblad No. 23 of 1948. Till this day, the regulation of Indonesian property law still uses the Civil Code originating from BW while the Netherlands itself has succeeded in amending its Civil Code in 1992 which we later call Nieuw Burgelijk Wetboek (NBW). Various changes have occurred in NBW, including those regarding property law. In contrast to BW, NBW only recognizes two types of division of properties, namely movable and immovable properties. This division is carried out in such a way by considering the interests of bezit, levering, bezwaring, verjaring, and beslag in property law. This article then tries to show that the division of property law in Indonesia through the interests of bezit, levering, bezwaring, verjaring, and beslag is still relevant to the current state of property law in Indonesia.Keywords : Property Law, Division of Properties, Interest on Division of Properties